Comparative perspectives on the development of canadian arctic shipping : impacts of climate change and globalization - Lasserre, Frédéric (Brill, 2023)
Climate change does impact sea ice, with a significant reduction of its extent and thickness. Climate change thus facilitates navigation, without making it easier, and indeed has contributed to the expansion of traffic in the Canadian Arctic, with a fivefold increase since 2000. However, there is a discrepancy between expectations that the melting of sea ice triggered and actual levels of shipping, especially regarding transit volumes. This can be accounted for by the fact that drivers of shipping in the Arctic, especially in Russian waters, are linked to the development of natural resources extraction and the perception that Arctic shipping markets may not readily fit into global strategies adopted by shipping companies. Potential economic drivers of Arctic shipping, extraction and transit, are related to the insertion of the region into globalized markets. With regard to climate change, conditions for the development of shipping in the Canadian and Russian Arctic are increasingly shaped by market, political and legal developments from outside the region, giving credence to the idea that the Arctic is increasingly inserted into the global economy. This chapter analyzes the evolution of Canadian Arctic shipping in the face of these developments.